Nitrogen and Phosphorus Efficiency on the Fruit Size and Yield of Capsicum - K. K. Pall2, S. S. Roy1*, M.S.I. Khan2 and K. K. (Journal of Experimental Sciences, 2011)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> A field experiment was conducted to study the effects of nitrogen and phosphorus on the fruit size and yield of Capsicum. The treatments comprised 4 levels of N (0, 50, 100 & 150 kg ha-1) and 3 levels of P (0, 30 & 60 kg ha-1). Length and breadth of fruit and number of fruits per plant increased significantly with increasing nitrogen doses up to 100 kg N ha-1. However, average weight of fruit content increased significantly up to 150 kg N ha-1. On the other hand, average weight of fruit and yield increased significantly with increasing levels of P up to the treatment 30 kg P ha-1, whereas length of fruit and number fruits per plant was increased significantly up to the 60 kg P ha-1. Considering the combined effect of nitrogen and phosphorus, the maximum significant length of Capsicum, breadth of Capsicum, number of fruits per plant and, average weight of fruit as well as yield were found in the treatment combination of 150 kg N and 30 kg P ha-1.